Simplification of Business Licensing in the Capital City of Nusantara - Nurini, Dyah Tutut Ika; Vitasari, Elly Vivi; Hadiyantina, Shinta; Kusuma, Ariska Cesar Divian Candra (Postgraduate Program in Law, Universitas Pattimura, 2026)
Introduction: This article analyzes the regime of business licensing facilitation in the Capital City of Nusantara (IKN) as mandated by the vision of IKN under Law Number 21 of 2023 on the Amendment to Law Number 3 of 2022 on the State Capital. The development of IKN holds both urgency and strategic significance for the national economy, thus requiring special policies that provide business licensing facilitation for entrepreneurs and investors.Purposes of the Research: The purpose of this study is to examine the underlying rationale for granting business licensing facilitation in IKN and to identify its specific forms through the policy of business licensing simplification.Methods of the Research: The research employs a normative juridical method using both the statute approach and the conceptual approach.Results Main Findings of the Research: The findings indicate that the rationale for facilitating business licensing in IKN can be viewed from three main aspects: ensuring clear legal certainty for every investment activity, reducing administrative barriers, and providing non-fiscal incentives to investors. These facilitation measures are implemented by the government through the simplification of business licensing procedures, starting from the fulfillment of basic licensing requirements to the commencement of business operations. The simplification of business licensing in IKN reflects the government’s commitment to promoting ease of doing business and providing incentives for business actors, while simultaneously supporting the acceleration of investment and infrastructure development by minimizing administrative burdens and licensing costs at the early stages of project implementation.